Nghiên cứu tổng hợp vật liệu polysunfat sắt, ứng dụng cho quá trình keo tụ - Thu Trang, Quản Thị; Giang, Lê Hà; Lâm, Phạm Văn (Vietnam Journal of Chemistry, 2017)
Polyferric sulfate (PFS) coagulant was prepared by hydrolysis co-polymerization from ferrous sulfate. In this paper, the role of major parameters, including ratio FeSO4:H2SO4, temperature of polymerization and ratio [OH]/[Fe] were investigated. The structure and morphology analysis were carried out by using FT-IR spectra, Scanning Electron Microscope (SEM) and X-ray diffraction (XRD). Finally, the coagulation efficiency of PFS in treating kaolin suspension and humic acid was evaluated. Keywords. Polyferric sulphate (PFS), coagulation.